Chinese herbal medicine Xianling Gubao capsule for knee osteoarthritis: A protocol for systematic review and meta-analysis. Issue 3 (21st January 2022) - Liu, Wang; Xu, Daoqing; Qi, Qi; Li, Jingjing; Ou, Liang
Abstract: Background: Knee osteoarthritis (KOA) is the most prevalent degenerative joint disease among populations over 60 years old, and is the most common cause of musculoskeletal pain and disability worldwide. Xianling Gubao capsule (XLGBC), a Chinese patent medicine, is widely used for treatment of osteoporosis. Meanwhile, according to the theory of homotherapy for heteropathy, XLGBC is increasingly applied in the clinical practice of KOA. However, no systematic review has found that XLGBC is as effective in treatment of KOA as it is in treatment of osteoporosis. Therefore, we will conduct a systematic review of XLGBC in KOA treatments. Methods: All randomized controlled trials assessing the validity of XLGBC therapy for KOA will be retrieved from the following seven databases, including the Cochrane Library, PubMed, EMBASE, Chinese Biomedical Literature Database, China National Knowledge Infrastructure, Wan Fang Database, and Chinese Scientific Journal Database. The primary outcome measures are the visual analogue scale pain score, and a comprehensive evaluation including the Western Ontario and McMaster Universities Arthritis Index scores, Lysholm scores, and Bristol scores. And the secondary outcome measures include cure rate and adverse events. The procedure such as retrieval and selection of literature, data extraction, evaluation of risk of bias, and assessment of reporting bias will be executed by 2 reviewers independently. The data synthesis for meta-analysis will be conducted by Review Manager 5.4 software. Results: A high-quality evidence of XLGBC for the treatment of KOA will be generated from the aspects of safety and efficacy. Conclusion: This systematic review will provide evidence to help us confirm the clinical efficacy of XLGBC in the treatment of KOA. OSF Registration number: Registration DOI 10.17605/OSF.IO/QD5SY.